Penggunaan Media Animasi Interaktif Dalam Membantu Pemahaman Siswa Pada Mata Pelajaran PAI di SMK An Nur Omben - Jamal, Nur; Baidowi, Achmad (AL -ALLAM, 2024)
In learning, teachers are not enough to just convey knowledge. However, they must also be able to raise the level of students' thinking from previous knowledge to the next level, namely understanding, so that the process of achieving learning objectives is more optimal. Therefore, teachers must be able to determine the best media to be used. Accuracy in the use of learning media greatly determines the creation of conducive and enjoyable conditions so as to provide opportunities for students to be more active in obtaining convenience in learning the subject matter presented by the teacher. This study aims to analyze the use of interactive animation media in helping students' understanding of Islamic Religious Education (PAI). With the rapid development of technology, interactive animation-based learning media are expected to help students' understanding. The focus of this study covers two aspects, namely: First, How is the Use of Interactive Animation Media in Helping Students' Understanding of PAI Subjects at SMK AN NUR OMBEN?. Second, What are the supporting and inhibiting factors for the Use of Interactive Animation Media in Helping Students' Understanding of PAI Subjects at SMK AN NUR OMBEN. This study uses a descriptive qualitative method. The data sources obtained were through interviews, observations and documentation, the informants were the principal of SMK AN NUR OMBEN, Deputy Curriculum, Islamic Religious Education Teachers, and Students of SMK AN NUR OMBEN.